Study on the Aplication of Conservative Islamics Boarding School Towards the Independence of Feed in Darul Fallah Bogor Islamic Boarding School - Nyai Mukholisah; Fani Rahayu; Yulia Apriana; Rahayu Lestari; Soni Prayoga; Nur Rochmah Kumalasari (Institut Pertanian Bogor, 2018)
Islamic boarding school or pondok pesantren is one of the islamic educational institutions that grow fastly in Indonesia. Some efforts that can be done to improve the quality of pondok pesantren can be done with conservation activities that is through land optimalization. Activity of land optimalization is a strategic effort that can be done in pesantren environment in order to maintain the existing land resources in pesantren supported by large enough land and enough human resources. Pesantren which do the activities of land optimalization continuously referred to conservation islamic boarding school or pesantren konservasi. The program of pesantren konservasi include activities of land optimalization conducted in the field of feed crops to develop the potential the sector of animal husbandry. Focus on the goal to be achieved is to support the better feed for the better food too. This study was conducted in March–May 2017, at Pondok Pesantren Darul Fallah, Ciampea, Bogor. The methods through several steps include the identification of islamic boarding school, get contacts of foundation management, observation of islamic boarding school application and assosiation. Beside that, practical activities in pesantren konservasi include the clearing of land area, crop selection, planting, and mentoring. In addition to creating an islamic boarding school environment-based, pesantren konservasi also helps to develop human resources that can compete in science and economics.